Are financing conditions a threat to SMEs' performance, growth, and transformation? - Annalisa Ferrando; Rozália Pál (Asian Development Bank Institute (ADBI), 2024)
Availability of internal and external financing sources has an impact on firms' investments and growth. Even profitable firms with sufficient financing sources in normal times can be affected by demand and supply shocks such as the COVID-19 lockdown, the energy crisis, or the recent tightening of financing conditions. This paper analyzes the impact of funding difficulties on firms' investment, performance, and growth during normal periods and periods of external shocks using a regression adjustment treatment effect approach. We differentiate among structural barriers of external financing and cyclical worsening of financing conditions, controlling for other major investment barriers. We use survey data collected from the first to the eighth vintage of the European Investment Survey (EIBIS). The empirical evidence shows that micro and small firms and leading innovators are particularly vulnerable to deteriorating funding conditions. Results indicate that firms' lagging in digitalization and green investments are facing more a structural rather than cyclical financing issue. Consequently, policy support should be oriented towards those structural financing impediments.
Keywords: C83; D22; G32; 330; SMEs; investment gap; external funding; internal funding; financing constraints; uncertainty; investment barriers; firm performance; growth; digital and green transition